The Ground Settlement and the Existing Pipeline Response Induced by the Nonsynchronous Construction of a Twin-Tunnel - Shicheng Sun; Chuanxin Rong; Houliang Wang; Linzhao Cui; Xin Shi (Advances in Civil Engineering)
Shielding tunnel construction always has negative impacts on the surrounding buildings. Because of repeated disturbances caused by the construction, more attention should be paid to the impacts of the nonsynchronous construction of a twin-tunnel. In this research, a three-dimensional model was established to simulate the construction process of a twin-tunnel in a section of the Hefei No. 4 metro line, and the calculation results were validated with the measured settlement data. Based on the model, the ground settlement and the existing pipeline responses were studied in detail. The results showed that, after the first tunnel (FT) construction, the settlement curves conformed to a Gaussian distribution. Additionally, after the second tunnel (ST) construction, the final settlement curves were no longer completely symmetrical. The influences of the twin-tunnel space and the pipeline-soil relative stiffness on the settlements were further studied. The results showed that the final settlement curves of the ground surface and the pipeline were mainly W-shaped, U-shaped, and V-shaped. As the twin-tunnel space increased and the pipeline-soil relative stiffness decreased, the settlement curve gradually changed from V-shaped to W-shaped. C was defined as the ratio of two maximum settlements in the W-shaped settlement curve. As the space increased, C started to decrease from 1 and then increased to 1.